A Review on Advanced Treatment of Pharmaceutical Wastewater - Guo, Y; Qi, P S; Liu, Y Z (IOP conference series. Earth and environmental science, 2017)
The composition of pharmaceutical wastewater is complex, which is high concentration of organic matter, microbial toxicity, high salt, and difficult to biodegrade. After secondary treatment, there are still trace amounts of suspended solids and dissolved organic matter. To improve the quality of pharmaceutical wastewater effluent, advanced treatment is essential. In this paper, the classification of the pharmaceutical technology was introduced, and the characteristics of pharmaceutical wastewater effluent quality were summarized. The methods of advanced treatment of pharmaceutical wastewater were reviewed afterwards, which included coagulation and sedimentation, flotation, activated carbon adsorption, membrane separation, advanced oxidation processes, membrane separation and biological treatment. Meanwhile, the characteristics of each process were described.